Synergistic Nanostructured MnOx/TiO2 Catalyst for Highly Selective Synthesis of Aromatic Imines. Issue 8 (23rd February 2021) - Sudarsanam, Putla; Köckritz, Angela; Atia, Hanan; Amin, Mohamad Hassan; Brückner, Angelika
Abstract: This work reports the development of a synergistic nanostructured MnOx /TiO2 catalyst, with highly dispersed MnOx nanoparticles (4.5±1 nm) on shape‐controlled TiO2 nanotubes (8–11 nm width and 120–280 nm length), for selective synthesis of valuable aromatic imines at industrially important conditions. Pristine TiO2 nanotubes exhibited 97 % imine selectivity at a 38.3 % benzylamine conversion, whereas very low imine selectivity was obtained over commercial TiO2 materials, indicating the catalytic significance of shape‐controlled TiO2 nanotubes. The MnOx nanoparticle/TiO2 nanotube (10 wt% Mn) catalyst calcined at 400 °C showed the best activity with 95.6 % benzylamine conversion and 99.9 % imine selectivity. This catalyst exhibited good recyclability for four times and is effective for converting numerous benzylamines into higher yields of imines. The high catalytic performance of MnOx /TiO2 nanotubes was attributed to higher number of redox sites (Mn 3+ ), high dispersion of Mn species, and shape‐controlled structure of TiO2, indicating that this catalyst could be a promising candidate for selective oxidation reactions. Abstract : Synergistic catalysis : An efficient catalytic strategy for synthesizing aromatic imines was reported over a nanostructured MnOx /TiO2 catalyst at industrially important conditions. The synergy between MnOx nanoparticles and TiO2 nanotubes led to improved catalytic properties, resulting in the highly selective synthesis of imines with good catalyst recyclability. This work can provide valuable insights for selective oxidation reactions.